Plasma activation and atomic layer deposition of TiO2 on polypropylene membranes for improved performances of lithium-ion batteries - Chen, H.; Lin, Q.; Xu, Q.; Yang, Y.; Shao, Zongping; Wang, Y. (Elsevier BV, 2014)
Atomic layer deposition (ALD) of TiO2 was applied on porous polypropylene (PP) membranes which were used as separators in lithium-ion batteries (LIBs) composed of Li4Ti5O12 (LTO) anode/Li cathode. Without plasma activation on the bare PP membrane, the initial deposition of TiO2 was based on the subsurface nucleation mechanism, which prevented the formation of a conformal hydrophilic TiO2 layer at low ALD cycles. The improvement of wettability of the PP membrane to the electrolyte could only be achieved at high ALD cycles up to 500. However, the severe narrowing of membrane pores counterbalanced the wetting enhancement, which hardly improved the performance of the LIBs. Plasma pretreatment was efficient to generate active groups on the highly chemically inert surface of polypropylene membranes, thus ultrathin TiO2 films could be conformally deposited by ALD on the membrane surface based on the layer-by-layer mechanism at cycles as low as 20. Such a conformal ultrathin layer of TiO2 was confirmed to concurrently overcome both the thermal shrinkage and poor wettability of the PP membranes. Beneficial from the improved wettability at no expense of pore size, the electrochemical performances of LIBs such as specific discharge capacities at different discharge rates were upgraded.